Effect of Work Discipline and Training on Employee Performance of PT Federal International Finance Depok Branch - Agrasadya Agrasadya (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study aims to determine the effect of work discipline and training on employee performance at PT. Federal International Finance Depok Branch. The method used is descriptive method with an associative approach, while to get the data done by distributing questionnaires to 90 respondents. The results of work discipline research have a positive and significant effect on employee performance by 33.10%. Hypothesis testing obtained tcount> ttable (6.205> 1.991), this is also strengthened by a probability of significance of 0,000 <0.05. Thus H0 is rejected and H1 is accepted meaning that there is an influence of work discipline on employee performance. Training has a positive and significant effect on employee performance by 44.7%. Hypothesis testing obtained tcount> ttable (7.939> 1.991), this is also strengthened with a significance probability of 0,000 <0.05. Thus H0 is rejected and H1 is accepted meaning that there is an influence of training on employee performance. Work discipline and training have a positive and significant effect on employee performance with a regression equation Y = 10.884 + 0.247X1 + 0.495X2. These results indicate the coefficient of work discipline variables of 0.247 and training of 0.495, all variables are positive meaning that the better discipline and training, the better the performance of employees. The contribution of the influence of work discipline and training was 50.3% while the remaining 49.7% was influenced by other factors. Hypothesis testing obtained Fcount> Ftable (46,364> 3,100) this is reinforced by the F-Probability significance of 0,000 <0.05, thus H0 is rejected and H3 is accepted meaning that there is a positive and significant influence between work discipline and training simultaneously on the performance of employees of PT. Federal International Finance Depok Branch.